Investigating the dynamics of hydrogen peroxide metabolism in the peroxiredoxin system of Saccharomyces cerevisiae - Badenhorst, Melinda (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.